2015
DOI: 10.31254/phyto.2015.4104
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic activity of ethanolic extract of aerial parts of Tribulus terrestris in mice

Abstract: Herbs have always been a preferred choice of treatment for people of the subcontinent and the Indo-Pak subcontinent has a long tradition of the use of herbs as medicines. In the given study ethanolic extract of Tribulus terrestris (EETT) has been screened for its anxiolytic potential in experimental mice using LDB, EPM and Head Dip models of anxiety. It showed an increase in the number of entries and time spent in the light compartment in LDM model. Further time spent in Open Arm has also been significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous study had shown that Tribulus terrestris has an important role in protecting the liver from toxic substances (10) . This plant acts as an antioxidant against free radicals (11,12) , anticancer, (13) metal chelator activity, hepatoprotective activity, anti-inflammatory effects (8) anxiolytic potential (14) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous study had shown that Tribulus terrestris has an important role in protecting the liver from toxic substances (10) . This plant acts as an antioxidant against free radicals (11,12) , anticancer, (13) metal chelator activity, hepatoprotective activity, anti-inflammatory effects (8) anxiolytic potential (14) .…”
Section: Introductionmentioning
confidence: 99%